2011
DOI: 10.1124/jpet.111.187179
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Inhibition of Constitutively Open N-Methyl-d-Aspartate Receptors

Abstract: N-Methyl-D-aspartate (NMDA) receptors gate a slow and calciumrich component of the postsynaptic glutamate response. Like all ionotropic glutamate receptors, NMDA subunits contain a highly conserved motif (SYTANLAAF) in the transmembrane (TM) 3 domain that is critically involved in channel gating. Mutation of an alanine in this domain (A7; underlined above) results in constitutively open receptors that show reduced sensitivity to several allosteric modulators. In this study, we examined the effects of ethanol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
(62 reference statements)
2
28
0
Order By: Relevance
“…Reports from our laboratory and others have identified a small number of amino acid residues located in the M3 and M4 domains of NMDA receptor GluN1 and GluN2 subunits that influence ethanol sensitivity and channel function (Ronald et al, 2001;Ren et al, 2003bRen et al, , 2007Honse et al, 2004;Smothers and Woodward, 2006;Xu et al, 2012). The determinants of ethanol sensitivity and receptor function at each of these positions differ markedly from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Reports from our laboratory and others have identified a small number of amino acid residues located in the M3 and M4 domains of NMDA receptor GluN1 and GluN2 subunits that influence ethanol sensitivity and channel function (Ronald et al, 2001;Ren et al, 2003bRen et al, , 2007Honse et al, 2004;Smothers and Woodward, 2006;Xu et al, 2012). The determinants of ethanol sensitivity and receptor function at each of these positions differ markedly from each other.…”
Section: Introductionmentioning
confidence: 99%
“…NMDA receptors are obligate heterotetramers composed of two glycine-binding GluN1 subunits interleaved with two glutamatebinding GluN2 subunits (Traynelis et al, 2010), and results from studies of both native and recombinant NMDA receptors suggest that ethanol acts as an allosteric modulator of receptor function (Chu et al, 1995;Mirshahi and Woodward, 1995;Peoples et al, 1997;Xu et al, 2012). Understanding where and how this allosteric modulation takes place is still not well understood, although recent studies by this laboratory and others have revealed potential sites of ethanol action within the transmembrane (TM) domains of the NMDA receptor (Ronald et al, 2001;Honse et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Site-directed mutagenesis was performed using the QuikChange XL mutagenesis kit (Agilent Technologies, Santa Clara, CA), and mutants were confirmed by DNA sequencing (GeneWiz, South Plainfield, NJ). NMDA structures were rendered using MacPymol (PyMOL Molecular Graphics System, Version 1.5.0.4; Schrödinger, New York, NY) using a homology model of the GluN1/GluN2A receptor described in a previous study (Xu et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations